2004
DOI: 10.1037/0012-1649.40.4.621
|View full text |Cite
|
Sign up to set email alerts
|

Reexamining the Vocabulary Spurt.

Abstract: The authors asked whether there is evidence to support the existence of the vocabulary spurt, an increase in the rate of word learning that is thought to occur during the 2nd year of life. Using longitudinal data from 38 children, they modeled the rate of word learning with two functions, one with an inflection point (logistic), which would indicate a spurt, and one without an inflection point (quadratic). Comparing the fits of these two functions using likelihood ratios, they found that just 5 children had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
158
0
8

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(195 citation statements)
references
References 41 publications
7
158
0
8
Order By: Relevance
“…Prior research on vocabulary growth in typical infants has demonstrated that the pace of acquisition accelerates as more words are acquired, which is typically captured by a quadratic component in the growth model (see e.g., Ganger & Brent, 2004;Fenson et al, 1994). For this reason we explored quadratic models in our comparison of vocabulary growth in preschool and infant adoptees.…”
Section: ______________________________________________________mentioning
confidence: 99%
“…Prior research on vocabulary growth in typical infants has demonstrated that the pace of acquisition accelerates as more words are acquired, which is typically captured by a quadratic component in the growth model (see e.g., Ganger & Brent, 2004;Fenson et al, 1994). For this reason we explored quadratic models in our comparison of vocabulary growth in preschool and infant adoptees.…”
Section: ______________________________________________________mentioning
confidence: 99%
“…That is, the later words sacrifice accuracy to range, while continuing to reflect a relatively restricted set of output forms. This second step in the widely evidenced U-shaped developmental profile is commonly accompanied by relatively rapid increase in new word production, often identified as a "lexical spurt" (although Ganger & Brent, 2004, cast some doubt on the quantitative validity of the term).…”
Section: Early Words and Templates Revisitedmentioning
confidence: 99%
“…The phonemes were not well represented in the phonological memory and therefore would not be available as building blocks for the construction of lexical representations. On the other hand, a low vocabulary acquisition impeded the use of words acquired as models to attain new words, phonetics rules and contrasts (Ganger and Brent, 2004). The role of phonology in the development of other domains, such as the lexicon and bound morphology, can be only identified through analyses of the phonological characteristics of early utterances of children at the same stage of lexical development.…”
mentioning
confidence: 99%